Between Constantinople and Constantinople: Nicaea as a capital and its role in 13th century - Leszka, Mirosław (Balcanica Posnaniensia. Acta et studia, 2012)
Bithynian Nicaea functioned as a capital of the Byzantine state for just under sixty years. Despite that temporariness, the city was able to perform a majority of the roles of the capital ‘Constantinopolitan style’. It was a residence of an emperor and a patriarch, a place of the imperial coronations, a centre of culture and science, a stately city under particular imperial protection. It lacked but one, irretrievable feature – it was not Constantinople itself. Michael Choniates wrote that Nicaea was a Babylon for the Byzantines and after completing their repentance there they would be allowed to return to the City, their ‘promised land’. That prophecy was fulfilled in the summer of 1261, when Constantinople fell into the hands of Michael VIII Palaeologus.